Nozzle Clogging in Vacuum Induction Melting Gas Atomization: Influence of the Delivery-Tube and Nozzle Coupling - Junfeng Wang; Min Xia; Jialun Wu; Changchun Ge (Archives of Metallurgy and Materials, 2022)
Nozzle clogging seriously affects the continuity of spraying powder in vacuum induction melting gas atomization (VIGA) process and increases the consumption of gas and raw materials. However, there are few systematic studies on nozzle clogging. This paper reports the physics of nozzle clogging in gas atomization production. The influence of coupling-length of different melt delivery-tubes on nozzle clogging is studied numerically and experimentally. The interface tracking method of Volume of Fluid (VOF) and the large eddy simulation (LES) model are performed for visualizing the melt droplets flow traces in primary atomization and the associated simulation cloud images compared with experimental results. Four delivery-tube coupling-lengths (0 mm, 3 mm, 5 mm, and 7 mm) relative to nozzle position and two gas pressures (3 MPa and 4.5 MPa) are chosen for this study. The results indicated that the coupling-lengths of 0 mm and 3 mm increases the strength of the recirculation zone, the melt droplets backflow is obvious, and the nozzle is blocked. However, this phenomenon eliminated with increasing coupling-lengths, the atomization process is continuous, but the final fine powder yield decreases. This research is of guiding significance and reference for understanding the nozzle clogging of vacuum induction melting gas atomization (VIGA) technology.